Seroprevalence and risk factors of Toxoplasma gondii infection in domestic raccoon dogs in four provinces in northern China. (March 2019) - Wang, Xin; Qin, Si-Yuan; Liu, Zheng-Liang; Zhang, Xiao-Tian; Cui, Dong-Yang; Li, Jing-Hao; Liu, Yan; Zhao, Quan; Ni, Hong-Bo
Abstract: Toxoplasma gondii is an obligate intracellular apicomplexan parasite that can infect almost all homoiothermal animals, including domestic raccoon dogs ( Nyctereutes procyonoides ). However, related reports on T. gondii infection in domestic raccoon dogs were limited in China. Therefore, a serological investigation was undertaken to investigate the seroprevalence and risk factors for T. gondii infection in domestic raccoon dogs. A total of 962 serum samples were collected from Jilin, Liaoning, Heilongjiang and Hebei provinces, northern China between April 2016 and November 2017, and were detected by the indirect hemagglutination test (IHA). The seroprevalence of T. gondii infection was 7.28% in the overall surveyed raccoon dogs by IHA, which was different among the four provinces ranging from 6.54% to 7.57%. The seroprevalence of T. gondii infection in male and female raccoon dogs was 6.62% and 7.79%, respectively. Based on statistical analysis, age was regarded as an important risk factor for T. gondii infection in raccoon dogs in this study ( P  < 0.05). This study reported the seroprevalence and risk factors of T. gondii infection in domestic raccoon dogs in northern China, which provided essential data for prevention and control of T. gondii infection in raccoon dogs in Jilin province, Liaoning province, Heilongjiang province and Hebei province. Highlights: The seroprevalence of T. gondii infection was 7.28%. This is the first record of T. gondii in raccoon dogs in Liaoning, Heilongjiang and Hebei, northern China. Age was regarded as an important risk factor for T. gondii infection in raccoon dogs in this study. These findings will provide useful data for the execution of control measures against T. gondii infection in many hosts.